Assigning Integration: A Framework for Intellectual, Personal, and Professional Development in Seminary Courses. (2nd January 2013) - Kanarek, Jane; Lehman, Marjorie
Abstract: This article explores assignments as a core teaching practice essential to integrating the cognitive, personal, and professional identities of seminary students. These core practices emerge in seminary curricula where there is a strong focus on the teaching of canonical texts and a goal of achieving textual mastery. We propose that carefully chosen and constructive assignments achieve the kind of integration necessary for building content knowledge and the professional, spiritual, and religious identities of our students. While the difference between the educational goals of clergy‐training in a seminary and training graduate students in the academy can be sharp, we argue here for ways to make that contrast both productive and generative.